Find the equation of the line that passes through (–3, 2) and the intersection of the lines x–2y=0 and 3x+y+5=0.
I need the intersection point of the lines and the equation of the line.

Respuesta :

Answer:

[tex]\frac{19}{7}[/tex]x+[tex]\frac{11}{7}[/tex]y+5=0

Step-by-step explanation:

the intersection of x-2y=0 and 3x+y+5 is ([tex]\frac{-10}{7}[/tex];[tex]\frac{-5}{7}[/tex])

=> the line : [tex]\frac{19}{7}[/tex]x+[tex]\frac{11}{7}[/tex]y+5=0

Answer:

[tex]Point \ of \ intersection = (\frac{-10}{7} , \frac{-5}{7})\\\\Equation \ of \ line : y = -\frac{19}{11}x - \frac{35}{11}[/tex]

Step-by-step explanation:

Find intersection of the given lines :

x - 2y = 0 => x = 2y ----------- ( 1 )

3x + y = - 5 -------------------- ( 2 )

Substitute ( 1 ) in ( 2 ) :

                               3x + y = - 5

                               3 ( 2y ) + y = - 5

                                6y + y = - 5

                                  7y = - 5

                                    [tex]y = -\frac{5}{7}[/tex]

Substitute y in ( 1 ) :

                            x = 2y

                           [tex]x = 2 \times \frac{-5}{7} = - \frac{10}{7}[/tex]

[tex]Therefore , \ point \ of \ intersection\ is ( -\frac{10}{7}, -\frac{5}{7} )[/tex]

To find the equation of the line passing through ( - 3, 2) and point of intersection :

Standard equation of a line : y = mx + b , where m is the slope, b is the y intercept.

So step 1 : Find slope , m:

 [tex]slope, m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]       [tex][ \ where \ (x_1, y_ 1 ) = ( -3, 2 ) \ and \ (x_2, y_ 2 ) = ( \frac{-10}{7} , \frac{-5}{7}) \ ][/tex]

              [tex]= \frac{\frac{-5}{7}-(2)}{\frac{-10}{7} - (-3)}\\\\= \frac{-5- 14}{-10 + 21}\\\\=\frac{-19}{11}\\\\=-\frac{19}{11}[/tex]

Step 2 : Equation of the line :

[tex](y - y _1) = m (x - x_1)\\[/tex]

[tex](y - 2 ) = -\frac{19}{11}(x -( -3))\\\\(y - 2 ) = -\frac{19}{11} (x+ 3)\\\\y = -\frac{19}{11} (x+ 3) + 2\\\\ y = -\frac{19}{11}x +(-\frac{19}{11} \times 3) + 2\\\\y= - \frac{19}[11}x +(\frac{-57}{11} + 2)\\\\y= - \frac{19}{11}x +(\frac{-57+ 22}{11})\\\\y= - \frac{19}{11}x +(\frac{-35}{11})\\\\[/tex]